Auditoría en seguridad vial, desde la Glorieta Punto 30 - Terminal de Transporte de Pereira. Km 27+600- Km 37+000 del departamento de Risaralda (2022)
The work presented below corresponds to implementing a Road Safety Audit, from the Glorieta Point 30 - Pereira Transport Terminal. Km 27+600- Km 37+000 of the department of Risaralda to the variables: barriers, geometric design of the road and signage, to establish its condition against the road actors that circulate through it, it was taken into account to carry it out under the methodology. quantitative - descriptive, and later proceeded to describe the most important parts of the state of the art, marked theoretical and conceptual, Through the use of data collection instruments such as checklists and various formats, field work was carried out to be able to develop each objective, the analysis of the results obtained from these can conclude that: the audited variables present faults that can turn them into accident points, but are not the cause of it, the recklessness of the driver followed by excessive speed and Inexperience in driving, recklessness of the pedestrian are the real cause of them, valid information in the rating of the matrices that shows that the risk value represents a tolerable risk, and the recommended actions would be to continue with driver education and carry out periodically preventive maintenance.